2013
DOI: 10.1155/2013/104913
|View full text |Cite
|
Sign up to set email alerts
|

Increased Resistance of Breast, Prostate, and Embryonic Carcinoma Cells against Herpes Simplex Virus in Three-Dimensional Cultures

Abstract: In previous studies we found that uveal melanoma cells grown in extracellular matrix (ECM)-containing three-dimensional (3D) cultures have increased resistance against herpes simplex virus type 1 (HSV-1)-mediated destruction relative to cells cultured without ECM. Using additional tumor cell types including MB-231 human breast cancer cells, PC-3 human prostate cancer cells, and P19 mouse embryonal carcinoma cells, we show here that tumor cell lines other than melanoma are also more resistant to HSV-1-mediated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 45 publications
(39 reference statements)
0
13
0
Order By: Relevance
“…Compared to traditional two-dimensional monolayer culture studies, 3D cultures have been shown to better simulate in vivo cellular behaviors such as growth, differentiation, invasion, and apoptosis ( 14 20 ). 3D cell cultures have also proven to be an effective design to study the interaction of HSV with tumor cells ( 12 , 13 , 23 , 24 ). Melanoma cells grown in 3D are more resistant to HSV-1 infection than cells grown in 2D, and HSV-1 may establish a quiescent infection in some melanoma cells in 3D cultures ( 12 , 13 ).…”
Section: Introductionmentioning
confidence: 99%
“…Compared to traditional two-dimensional monolayer culture studies, 3D cultures have been shown to better simulate in vivo cellular behaviors such as growth, differentiation, invasion, and apoptosis ( 14 20 ). 3D cell cultures have also proven to be an effective design to study the interaction of HSV with tumor cells ( 12 , 13 , 23 , 24 ). Melanoma cells grown in 3D are more resistant to HSV-1 infection than cells grown in 2D, and HSV-1 may establish a quiescent infection in some melanoma cells in 3D cultures ( 12 , 13 ).…”
Section: Introductionmentioning
confidence: 99%
“… 50 Later, the same group extended the experiments with breast, prostate, and embryonic cancer cells. 51 In this work, they found differences in growth patterns among the varying cells in three-dimensional cell cultures and obvious differences in common two-dimensional cell cultures. With herpes simplex virus 1 (HSV1), their results indicated massive inhibition of viral penetration through Matri-gel.…”
Section: Culture Systems Utilizing Hydrogels In Oncolytic Virotherapymentioning
confidence: 64%
“…In summary, at least two mechanisms of resistance in Matrigel cell cultures were found: on one hand, the physical Matrigel barrier working quite efficiently against viral distribution and spread, and on the other, the ECM-mediated suppression of viral replication ( Table 3 ). 50 , 51 …”
Section: Culture Systems Utilizing Hydrogels In Oncolytic Virotherapymentioning
confidence: 99%
“…The extracellular matrix and areas of tissue necrosis, which can be seen in high-grade tumors, may impair the spread of oHSV. 79 , 80 Of note, many pediatric high-grade tumors, such as Ewing sarcoma, neuroblastoma, rhabdomyosarcoma, and medulloblastoma to name a few, are classified as small round blue cell tumors. Histologically these tumors are highly cellular and composed of tight sheets of small, round cells with scant cytoplasm.…”
Section: Challenges and Arming Strategiesmentioning
confidence: 99%